(untitled) (Research, Society and Development, 2020)
Article theme is teacher training. Objective is to discuss the continuing teacher education, based on LDB/1996 and Resolution CNE-CP n. 2/2015 (DCN/2015). Methodologically, the research is qualitative, of bibliographic-documental character, relying on authors who study the subject, such as Imbernón, Freire, Gatti and Alvarado-Prada, Freitas and Freitas, among others, and in official regulations (Federal Constitution, laws, decrees and guidelines). The concepts of State, public policies and educational policies and their relations in the context of contemporary society are addressed; literary aspects of continuing teacher education are discussed; and it is analyzed the continuing teacher education at LDB/1996 and DCN/2015. It is concluded that the relationship between State, public policies and educational policies is conditioned by the demands of the labor market, through specific forms of intervention in education, such as the concept of teacher education; that continuing teacher education is fundamental for reading educational reforms and the consequent reflection on professional (de)valorization; that DCN/2015 envisages an advance in continuing teacher training leading to the qualification of educational practice, through possibilities of innovation in educational pedagogical practices; and that LDB/1996 went backwards, as the admission to the teaching profession of professionals with notorious knowledge, denying the existence of specific knowledge of teaching and the valorization of the profession.